The Analysis of Assessment and Psychological Assistance Services to Find Out the Causes and Impacts of Violence Against Women and Children - Muhammad Akbar Rizkhianzah; Siti Jaro'ah (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2024)
Violence against women and children is becoming increasingly widespread and rising each year, severely impacting their psychological well-being. Victims can experience severe psychological disorders such as depression and anxiety if they don’t receive effective interventions. Institutions like the Unit Pelaksana Teknis Perlindungan Perempuan dan Anak (UPT PPA) in East Java provide protection and a sense of security for victims until their psychological condition recovers. This study combines documentary research with interviews and field observations to examine the psychological dynamics and common causes of violence against women and children. It also reviews the effectiveness of psychological interventions provided by UPT PPA in East Java. Findings indicate that violence is often caused by low self-control and influenced by factors such as frustration and deep-rooted patriarchal culture in society. The most dominant impact of violence is psychological, including anxiety, depression, and prolonged deep fear. However, psychological disorders in victims have been successfully stabilized through a series of assessments and psychological interventions conducted by UPT PPA in East Java. This reveals that the assessment process and psychological support provide positive impacts and direct social support for the recovery process from the trauma of victims.